PENGGUNAAN HUKUM SEBAGAI INSTRUMEN KEBIJAKAN PUBLIK DALAM PENGANGKUTAN LAUT NASIONAL - Cokorde Istri Dian Laksmi Dewi; Ni Luh Nila Winarni (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Ngurah Rai, 2020)
Indonesia as the maritime state with 67% of its territory is aquatic region of 17,000 islands, requiring a good regulation on the national shipping system. For the creation of a national oceanic system capable of meeting the need for transportation in Indonesia the law can become an instrument in establishing public policy on national transport, a because on national transportation not regulated in the rule-the trade law law (KUHD) but regulated in the 1988 government regulation number 17 on the provision and company of ocean transport. The problem is 1) how can the law be a public policy instrument in national ocean transport and, 2) what public policy model is used in national ocean transport ?To answer that using a qualitative descriptive research method that describes patterns to understand the phenomenon of what experienced by the subjects of the study. So it is concerned that the use of law as a public policy instrument in the national transportation of the sea is as a legal umbrella of any government action in connection with the transport of the national sea by applying the public policy model of the group where the government becomes mediator through policies issued from various groups of interests that organize marine transport services. The government needs to set the rules of maintaining the interests of each business and consumer.